Leucoagaricus houaynhangensis (Agaricaceae), a new yellowish-green species from Lao People’s Democratic Republic - Phongeun Sysouphanthong (2018)
© 2018, Chiang Mai University. All rights reserved. Leucoagaricus houaynhangensis, a yellowish-green agaric species, is described as a new species from Laos. It is characterised by light yellow to yellowish-green basidioma, covered with dark to dark grayish-brown squamules on pileus, free lamellae, subcylindrical and smooth stipe, membranous and fragile annulus, oblong ovoid and hyaline basidiospore with a germ pore, clavate and 4-spored basidia, clavate to utriform cheilocystidia with slightly a long apical appendage, a hymeniderm pileus covering made up of cylindrical elements, a cutis stipe covering made up of cylindrical elements and absence of clamp-connections in all tissue. Photographs on field and illustrator line drawing of microscopic characters are given. Two known species, La. flavovirens J.F. Liang, Zhu L. Yang & J. Xu and La. viridivavus (Petch) T.K.A. Kumar & Manim., share some morphological similarities with the newly described taxon here, but they difference by both morphological characters and nrITS DNA.